Understanding Prepositions - "Sargeant, Howard" (Learners Publishing Pte Ltd: Singapore, 2004)
This book offers advice on recognising, understanding and using prepositions correctly. In the study section, the role of prepositions in phrasal verbs is explained and analysed, and in the reference section the prepositions are listed alphabetically, and their uses are illustrated with numerous examples
Keywords: English language